5-HT1A receptor-mediated activation of neuroendocrine responses and multiple protein kinase pathways in the peripubertal rat hypothalamus. (1st September 2018) - Petrunich-Rutherford, Maureen L.; Garcia, Francisca; Battaglia, George
Abstract: Increasing evidence suggests that multiple factors can produce effects on the immature brain that are distinct and more long-lasting than those produced in adults. The hypothalamic paraventricular nucleus (PVN) is a region integral to the hypothalamic-pituitary-adrenal axis and is affected by anxiety, depression, and drugs used to treat these disorders, yet receptor signaling mechanisms operative in hypothalamus prior to maturation remain to be elucidated. In peripubertal male rats, systemic injection of the selective serotonin 1A (5-HT1A ) receptor agonist (+)8-OH-DPAT (0.2 mg/kg) markedly elevated plasma levels of oxytocin and adrenocorticotropic hormone (ACTH) at 5 and 15 min post-injection. The 5-HT1A receptor selectivity was demonstrated by the ability of the 5-HT1A receptor selective antagonist WAY100635 to completely block both oxytocin and ACTH responses at 5 min, with some recovery of the ACTH response at 15 min. At 15 min post-injection, (+)8-OH-DPAT also increased levels of phosphorylated extracellular signal-regulated kinase (pERK) and phosphorylated protein kinase B (pAkt) in the PVN. As previously observed in adults, (+)8-OH-DPAT reduced levels of pERK in hippocampus. WAY100635 also completely blocked (+)8-OH-DPAT-mediated elevations in hypothalamic pERK and pAkt and the reductions in hippocampal pERK, demonstrating 5-HT1A receptor selectivity of both kinase responses. This study provides the first demonstration of functional 5-HT1A receptor-mediated ERK and Akt signaling pathways in the immature hypothalamus, activated by a dose of (+)8-OH-DPAT that concomitantly stimulates neuroendocrine responses. This information is fundamental to identifying potential signaling pathways targeted by biased agonists in the development of safe and effective treatment strategies in children and adolescents. Highlights: 5-HT1A receptors activate ERK and Akt in peripubertal rat hypothalamic PVN. 5-HT1A receptors activate oxytocin and ACTH responses in peripubertal rat PVN. WAY100635 blocks (+)8-OH-DPAT-induced neuroendocrine responses. WAY100635 blocks (+)8-OH-DPAT-induced alterations in pERK and pAkt. 5-HT1A receptors are coupled to multiple signaling pathways in peripubertal PVN.